Adaptogenic activity of Cinnamomum camphora, Eucalyptus globulus, Lavandula stœchas and Rosmarinus officinalis essential oil used in North-African folk medicine - Boumendjel, Mahieddine; Boucheker, Abdennour; Feknous, Sandra; Taibi, Faiza; Rekioua, Naouel; Bouzeraa, Nawel; Chibi, Asma; Feknous, Nesrine; Baraoui, Allaeddine; N’har, Salem; Toubal, Azzeddine; Taguida, Amira; et al. (Cellular and Molecular Biology, 2021)
Depressive anxiety is one of the most emotional disorders in our industrial societies. Many treatments of phobias exist and are based on plant extracts therapies, which play an important role in the amelioration of the behavior. Our study aimed to evaluate the adaptogenic activity of different essential oils provided from local plants: Cinnamomum camphora (Camphora), Eucalyptus globulus (Blue gum), Lavandula stœchas (Topped lavender) and Rosmarinus officinalis (Rosemary) on Wistar rats. The adaptogenic activity was evaluated on the elevated plus-maze. The efficacy of the extract (200 mL/kg) was compared with the standard anxiolytic drug Diazepam® 1 mg. Animals administered by the essential oil of Lavandula stœchas, Cinnamomum camphora, Rosmarinus officinalis and Eucalyptus globulus showed a behavior similar to those treated with Diazepam®. For groups treated with the following essential oils: Rosmarinus officinalis, Lavandula stoechas and Cinnamomum camphora at a dose of 200 mL/kg, we notice an increase in the time spent on the open arms of the elevated plus-maze and a decrease in time spent on the closed arms of the elevated plus-maze, especially for Rosmarinus officinalis, which explains the anxiolytic effect of these plants. We also notice a decrease in the number of entries in closed arms, open arms and the number of passing to the central square. The increase in the number of entries to open arms with Eucalyptus globulus essential oil shows a reduction in anxiety behavior in rodents and this shows that these plants have an inhibitory effect.